KARAKTERISTIK IBU YANG MELAHIRKAN BAYI DENGAN BAYI BERAT LAHIR RENDAH - Muji Rahayu, Ria; Eka Redowati, Tusi (Jurnal Kesehatan, 2023)
Low Birth Weight Babies (LBW) are the cause of infant death in Indonesia. LBW is at risk of causingcomplications such as hypothermia, hypoglycemia, hyperglycemia, impaired immunity, breathing andthe circulatory system. This study aims to determine the characteristics of mothers who give birth tobabies with LBW at Permata Hati Hospital, Metro City. The method in this study is descriptive, theobject of this study is Age, Parity, and Occupation with LBW events. The population in this study wereall mothers who gave birth to babies with LBW, totaling 183 people with a total sampling technique.The data collection tool in this study used a checklist sheet. By using univariate analysis. The resultsshowed that the age frequency distribution of 183 respondents mostly belonged to the age of 20-35years, namely as many as 145 people (79.23%), the distribution of parity frequencies mostly belongedto primipara parity, namely 91 people (49.73%), and the distribution of frequency of work most of therespondents did not work as many as 167 people (91.26%). The conclusion in this study is that themajority of respondents are aged 20-35 years, the parity of respondents is primipara and the majorityof respondents do not work. So it is recommended that health workers try to carry out good andcomprehensive antenatal care, and encourage pregnant women to have a pregnancy check up at leastfour times during pregnancy.